The Relationship between the Quality of Nursing Services and the Satisfaction of Inpatients at the Mukomuko Regional General Hospital in 2022 - Zaleha, Siti; Handayani, Tita Septi; Rustandi, Handi (Universitas Dehasen Bengkulu, 2023)
The hospital is a complete individual health service organization that provides inpatient, outpatient, and emergency services provided for the benefit of the community in terms of improving the quality of life (Johan, 2005). One that determines patient satisfaction is the quality of nursing services on the quality of health services, in fact it is one of the determining factors for the image of health service institutions (hospitals) in the eyes of the public (Hayati 2010). Customer satisfaction is a key determinant of service demand levels and supply functions or operations. The purpose of this study was to determine the relationship between the Quality of Nursing Services and the Satisfaction of Inpatients at the Mukomuko Regional General Hospital in 2022 This type of research is a descriptive quantitative research using a cross sectional approach. Sampling used accidental sampling technique with the number of respondents 75 inpatients in class 1, 2 and class 3 at the Mukomuko Regional General Hospital. Statistical tests in this study used the frequency distribution test on univariate analysis and the chi-square test on bivariate analysis.The results showed that the quality of nursing services at the Mukomuko Regional General Hospital was mostly good, most of the respondents felt high satisfaction, and the results of the chi-square analysis showed that there was a relationship between the quality of nursing services and the satisfaction of inpatients at the Regional General Hospital. Mukomuko Year 2022 p value 0.000 < α = 0.05. Through this research, it is hoped that nurses can improve the quality of service in inpatient rooms in order to increase patient satisfaction which will lead to a comprehensive quality of hospital services.